Epizootic Monitoring of Avian Pasteurellosis in Broiler Chickens Under the Conditions of Nukus City - G. T, Nsanbayeva; F. S, Pulotov (American Journal of Botany and Bioengineering, 2026)
This article presents the results of field monitoring conducted to assess the epizootic situation of avian pasteurellosis among broiler chickens under the conditions of Nukus city, Republic of Karakalpakstan. During the study, a clinical examination was carried out in poultry farms engaged in broiler production. In birds suspected of the disease, the general condition, respiratory system, mucous membranes, body covering, fecal characteristics, and epizootic indicators of poultry farms were examined. In addition, blood samples were collected from the birds, properly labeled, and sent to the laboratory for further laboratory investigations. The monitoring results indicate the necessity of early detection of pasteurellosis, proper organization of differential diagnosis, and strengthening of biosecurity measures in broiler farms.